2001
DOI: 10.1016/s0926-3373(01)00171-0
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assisted catalytic reduction of sulfur dioxide with methane over MoS2 catalysts

Abstract: The catalytic reduction of sulfur dioxide with methane to form carbon dioxide and sulfur has been studied over MoS 2 /Al 2 O 3 catalysts. The reaction has been found to occur with microwave (2.45 GHz) heating at recorded temperatures as much as 200 • C lower than those required when conventional heating was used. An activation energy of 117 kJ mol −1 has been calculated for the conventionally heated reaction, but an Arrhenius analysis of the data obtained with microwave heating was not possible, probably becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 22 publications
1
54
0
Order By: Relevance
“…For the catalytic decomposition of H 2 S [16], where an apparent equilibrium shift was also observed, the hot-spot temperatures were found 100-200 C higher than the temperature measured by the optical thermometer. In the study on the reduction of SO 2 with CH 4 [21], it was found that some regions of the catalyst reached temperatures which were approximately 200 C in excess of the measured temperature. In the present study, it was noticed that, when the temperature was increased, in particular, above 700 C, the difference between the conversions under microwave and conventional heating became small for both CO 2 and CH 4 conversions and the temperature difference between the hot spots and the bulk catalyst bed was in the range of 0 to 100 C. These results could not be explained simply by a constant difference in the effective temperature of reactions.…”
Section: Conversions Of Co 2 and Ch 4 As A Function Of Temperaturementioning
confidence: 92%
“…For the catalytic decomposition of H 2 S [16], where an apparent equilibrium shift was also observed, the hot-spot temperatures were found 100-200 C higher than the temperature measured by the optical thermometer. In the study on the reduction of SO 2 with CH 4 [21], it was found that some regions of the catalyst reached temperatures which were approximately 200 C in excess of the measured temperature. In the present study, it was noticed that, when the temperature was increased, in particular, above 700 C, the difference between the conversions under microwave and conventional heating became small for both CO 2 and CH 4 conversions and the temperature difference between the hot spots and the bulk catalyst bed was in the range of 0 to 100 C. These results could not be explained simply by a constant difference in the effective temperature of reactions.…”
Section: Conversions Of Co 2 and Ch 4 As A Function Of Temperaturementioning
confidence: 92%
“…), which could be placed either in a cylindrical microwave cavity or in a conventional furnace [16,17]. A directional coupler was inserted into the microwave guide system so that the amount of microwave power reflected from the cavity could be measured.…”
Section: Methodsmentioning
confidence: 99%
“…The research has been focused on the application of microwave dielectric heating in a range of chemical processes including the synthesis of superconducting ceramics [31] and other inorganic materials [33][34][35][36][37][38][39][40][41], the synthesis of organometallic compounds [42,43], solid-state reactions involving metal powders [44][45][46][47][48], and more recently heterogeneous catalytic reactions [49][50][51][52][53][54][55]. Advances have also been made in understanding dielectric heating behaviour [24,29,50,52,56].…”
Section: Introductionmentioning
confidence: 99%